Genome-Wide Identification of Apple Atypical bHLH Subfamily PRE Members and Functional Characterization of MdPRE4.3 in Response to Abiotic Stress - Li, Tong; Shi, Yan; Zhu, Baihui; Zhang, Tianen; Feng, Ziquan; Wang, Xiaofei; Li, Xiuming; You, Chunxiang (Frontiers in Genetics, 2022)
Paclobutrazol Resistance (PRE) genes encode atypical basic helix–loop–helix (bHLH) transcription factor family. Typical bHLH proteins contain a bifunctional structure with a basic region involved in DNA binding and an adjacent helix–loop–helix domain involved in protein–protein interaction. PRE members lack the basic region but retain the HLH domain, which interacts with other typical bHLH proteins to suppress or enhance their DNA-binding activity. PRE proteins are involved in phytohormone responses, light signal transduction, and fruit pigment accumulation. However, apple (Malus domestica) PRE protein functions have not been studied. In this study, nine MdPRE genes were identified from the apple GDDH13 v1.1 reference genome and were mapped to seven chromosomes. The cis-acting element analysis revealed that MdPRE promoters possessed various elements related to hormones, light, and stress responses. Expression pattern analysis showed that MdPRE genes have different tissue expression profiles. Hormonal and abiotic stress treatments can induce the expression of several MdPRE genes. Moreover, we provide molecular and genetic evidence showing that MdPRE4.3 increases the apple’s sensitivity to NaCl, abscisic acid (ABA), and indoleacetic acid (IAA) and improves tolerance to brassinosteroids (BR); however, it does not affect the apple’s response to gibberellin (GA). Finally, the protein interaction network among the MdPRES proteins was predicted, which could help us elucidate the molecular and biological functions of atypical bHLH transcription factors in the apple.